The diagnosis, treatment and follow-up of extracranial carotid stenosis: a multidisciplinary German-Austrian guideline based on evidence and consensus - Eckstein, Hans-Henning; Kühnl, Andreas; Dörfler, Arnd; Kopp, Ina B.; Lawall, Holger; Ringleb, Peter A. (Deutsches Ärzteblatt, 2013)
BACKGROUND: Extracranial atherosclerotic lesions of the carotid bifurcation cause 10% to 20% of all cases of cerebral ischemia. Until now, there have been no comprehensive evidence- and consensus-based recommendations for the management of patients with extracranial carotid stenosis in Germany and Austria. - METHODS: The literature was systematically searched for pertinent publications (1990-2011). On the basis of 182 randomized clinical trials (RCTs) and 308 systematic reviews, 30 key questions were answered and evidence-based recommendations were issued. - RESULTS: The prevalence of extracranial carotid stenosis is more than 5% from age 65 onward. Men are affected twice as frequently as women. The most important diagnostic technique is Doppler- and color-coded duplex ultrasonography. RCTs have shown that the treatment of high-grade asymptomatic carotid stenosis with carotid endarterectomy (CEA) can lower the 5-year risk of stroke from 11% to 5%. Intensive conservative treatment may lower the stroke risk still further. Moreover, RCTs have shown that CEA for symptomatic 50% to 99% carotid stenosis lowers the 5-year stroke risk by 5% to 16%. Meta-analyses of the 13 available RCTs comparing carotid artery stenting (CAS) with CEA have shown that CAS is associated with a 2% to 2.5% higher risk of periprocedural stroke or death and with a 0.5% to 1% lower risk of periprocedural myocardial infarction. If no particular surgical risk factors are present, CEA is the standard treatment for high-grade carotid stenosis. CAS may be considered as an alternative to CEA if the rate of procedure-related stroke or death can be kept below 3% or 6% for asymptomatic and symptomatic stenosis, respectively. - CONCLUSION: Further studies are needed so that better selection criteria can be developed for individually tailored treatment.
Gesehen am 08.01.2021